181k views
3 votes
Which of the following is a solution to the system of equations?
y= 3x-2
6 + y=-x

User Roe
by
5.1k points

2 Answers

5 votes

Answer:

(-1, -5)

Explanation:

We can solve this system using substitution. y = 3x - 2, so replace "y" in the second equation with "3x - 2:"

6 + (3x - 2) = -x, or 6 + 3x - 2 = -x

Group like terms together: 3x + x = -6 + 2.

Then 4x = -4, and x = -1.

Subst. -1 for x in the first equation: y = 3(-1) - 2, or y = -5.

Then the solution is (-1, -5).

User AMTourky
by
5.0k points
4 votes

Answer:

x=-1 y = -5

Explanation:

y= 3x-2

6 + y=-x

Substitute the first equation into the second equation

6 +y =-x

6+ (3x-2) = -x

Combine like terms

4 + 3x = -x

Subtract 3x from each side

4 +3x -3x = -x -3x

4 = -4x

Divide by -4

4/-4 = -4x/-4

-1 =x

Now we need to find y

y= 3x-2

y = 3(-1) -2

= -3-2

= -5

User Nguyen Thanh Son
by
5.0k points